2011
DOI: 10.4321/s0213-61632011000400001
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity patterns in dual diagnosis across seven European sites

Abstract: -Background and Objectives: Psychiatric inpatients with substance use disorders are a significant public health concern due to grave consequences including increased risk of self harm, homicide as well as poor clinical outcome. The present study aims to examine and compare patterns of comorbidity (i.e. concurrent substance use disorders and severe mental illness) among psychiatric inpatients across seven European sites. 180 K. CHARZYNSKA ET AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Individuals with co-morbidity of substance and psychiatric disorders are more likely to be unemployed, homeless, and violent and have family and interpersonal relationship instability [22,23]. They tend to experience victimization, social exclusion, legal problems, and a greater prevalence of acquiring communicable diseases like HIV or Hepatitis, due to their risk-taking behaviors [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with co-morbidity of substance and psychiatric disorders are more likely to be unemployed, homeless, and violent and have family and interpersonal relationship instability [22,23]. They tend to experience victimization, social exclusion, legal problems, and a greater prevalence of acquiring communicable diseases like HIV or Hepatitis, due to their risk-taking behaviors [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of psychiatric co-morbidity found in this population (e.g., Charzynska et al, 2011 ; Rao, 2019 ; Rao et al., 2021 ; RCPSYCH, 2018 ; Searby et al, 2015 ) points to a complex relationship between the psychosocial characteristics of late-onset problem drinkers and poor mental health ( Bruce, 2002 ; Emiliussen et al, 2017d ; Shaw & Palattiyil, 2008 ; Ward et al, 2008 ; WHO, 2020 ). Indeed, 12 of the papers in the current review (almost half) reported psychiatric co-morbidity in their participants (see Table 9 ).…”
Section: Narrative Synthesismentioning
confidence: 92%
“…In total, 13.5% of the substance use disorders in this data were related to narcotics and 13.5% to stimulant drugs. (Charzynska et al, 2011. ) Inside the discipline of addiction psychiatry, there are both outpatient and inpatient units.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 11.8% of patients were diagnosed with bipolar disorder and 9.8% with depression. (Charzynska et al , 2011.) A national survey of drug-using clients in substance addiction services stated that narcotics were the main drugs causing problems for 40% of the clients and stimulant drugs (mainly amphetamine) for 21%.…”
Section: Introductionmentioning
confidence: 99%